The Analysis of Factors That Affecting the Tourist Visiting in Minahasa Regency - Stanny S Rawung (Journal of International Conference Proceedings (JICP), 2018)
The Minahasa Regency is the first district that was formed in North Sulawesi Province. Geographically the location of Minahasa Regency is quite strategic. Minahasa Regency is directly adjacent to several districts and the capital of North Sulawesi Province, Manado, which is the economic and government center in North Sulawesi Province. Tourism areas in Minahasa Regency consist of cultural tourism, natural tourism and artificial tourism. Cultural tourism includes historical heritage sites such as Batu Pinabetengan, Benteng Moraya and Tombs of National Heroes. Natural tourism in Minahasa Regency consists of beaches, lakes, waterfalls and hot springs. Artificial tourism is Bukit Kasih in the kawangkoan Barat sub-district and Horse Racing in Tompaso sub-district. Tourism is one sector that is the mainstay of the government to generate regional income and expand employment opportunities, in addition to introducing national and regional identities and cultures. Tourism development can be done by expanding and utilizing regional tourism potential. The Long-Term Development Plan for 2010-2025 in Minahasa District stipulates that the area is one of the tourist destinations in North Sulawesi. In fact, the number of domestic and foreign tourist arrivals to the district is still far from what is expected, the purpose of this study is: (1) To find out more about the factors that influence tourist visits in Minahasa Regency (2) To find out more what is the potential competitiveness of tourism in Minahasa Kabuaten compared to other Districts / Cities in North Sulawesi Province. This type of research is primary research using descriptive quantitative approach. Data sources used in this study are primary data that is obtained through survey data collection techniques. Secondary data used in this study are scientific publications issued by related parties, for example the BPS and the Minahasa Regency Tourism and Culture Office. The population in this study were all foreign tourists and domestic tourists who visited the tourist objects in the Minahasa Regency. For the study sample, researchers took samples accidentally against tourists who visited Bukit Kasih Kanonang and Benteng Moraya Tondano. Each of the 50 people for each place. The total sample in this study was 100 tourists. The research questionnaire was arranged based on the research variables, namely: the quality of human resources, the promotion of tourism, facilities - tourism infrastructure. The collected data is analyzed using percentages. Where the percentage is expected to reflect the most dominant factor influencing tourist visits in Minahasa Regency. Keywords: Tourist Visits, Minahasa Regency Tourism, Affecting Factors